SMART FARMING 4.0 UNTUK MEWUJUDKAN PERTANIAN INDONESIA MAJU, MANDIRI, DAN MODERN - Rika Reviza Rachmawati (Forum penelitian Agro Ekonomi, 2020)
Smart farming 4.0 based on artificial intelligence is a flagship launched by the Ministry of Agriculture. Smart farming 4.0 encourages the farmers to work more efficient, measurable, and integrated. Through technology, farmers are able to carry out farm practice by relying on mechanization, not on the planting season, from planting to harvesting accurately. Several smart farming technologies such as blockchain for modern off farm agriculture, agri drone sprayer, drone surveillance (drone for land mapping), soil and weather sensors, intelligent irrigation systems, Agriculture War Room (AWR), siscrop (information systems) 1.0 have been implemented in some areas. However, farmers deal with various educational backgrounds, aging farmers phenomenon, and high cost of smart farming technology tools to implement smart farming. This paper aims to analyze the huge opportunities of smart farming by utilizing the potential of millennial farmers as actors and analyzing various government policies to support smart farming 4.0. The Ministry of PDTT has carried out pilot projects to implement smart farming in several locations. The Ministry of Agriculture also needs to play a role by creating a smart farming roadmap. The Government's Strategic Project 2020–2024 through food estate based on farmer corporations may support massive smart farming applications.